2013
DOI: 10.1167/13.13.27
|View full text |Cite
|
Sign up to set email alerts
|

A proto-object-based computational model for visual saliency

Abstract: State-of-the-art bottom-up saliency models often assign high saliency values at or near high-contrast edges, whereas people tend to look within the regions delineated by those edges, namely the objects. To resolve this inconsistency, in this work we estimate saliency at the level of coherent image regions. According to object-based attention theory, the human brain groups similar pixels into coherent regions, which are called proto-objects. The saliency of these proto-objects is estimated and incorporated toge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Scene processing begins with a massive array of visual information that is sampled during eye fixations. The array is subdivided and grouped into potential objects and background structures during early and intermediate visual processing (e.g., Itti & Koch, 2000;Xu & Chun, 2009;Yanulevskaya et al, 2013). Determining object and region boundaries is complex, because stimulus information is locally ambiguous, as has been noted (e.g., Granlund, 1999;Tsotsos, 1990Tsotsos, , 2001.…”
Section: Early Scene Perceptionmentioning
confidence: 99%
See 2 more Smart Citations
“…Scene processing begins with a massive array of visual information that is sampled during eye fixations. The array is subdivided and grouped into potential objects and background structures during early and intermediate visual processing (e.g., Itti & Koch, 2000;Xu & Chun, 2009;Yanulevskaya et al, 2013). Determining object and region boundaries is complex, because stimulus information is locally ambiguous, as has been noted (e.g., Granlund, 1999;Tsotsos, 1990Tsotsos, , 2001.…”
Section: Early Scene Perceptionmentioning
confidence: 99%
“…Conscious identification of an object requires individuation (e.g., Xu & Chun, 2009). Different regions of the processed scene compete with each other for individuation, and the likelihood that a region will win (be individuated and represented) increases with stimulus factors such as the region's size and contrast from the background (e.g., Itti & Koch, 2000;Yanulevskaya et al, 2013). In regions away from the center of fixation (parafoveal and peripheral regions), the competition for individuation becomes especially high, because neural resources are increasingly scarce; as a result, objects crowd other objects and make them consciously imperceptible (e.g., Whitney & Levi, 2011).…”
Section: Early Scene Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ultimate goal is, however, to utilize GTOM approaches to non-artificial stimuli or stimuli where an object segmentation is simply not available. For these applications, gaze processing has to be combined with vision algorithms (e.g., proto-object maps [Yanulevskaya et al 2013]) that can automatically segment parts in an image which a user perceives as objects.…”
Section: Discussionmentioning
confidence: 99%
“…To link objectness with saliency, local saliencies were computed in randomly sampling a large number of windows [27,28]. Recent study [29] suggested that the unit of attention depends on the task, the field of view and the observer's intention. Object proposal generation and salient object detection are tightly linked among human subjects [21].…”
Section: Introductionmentioning
confidence: 99%